Human Resources Development Model For The Industrial Revolution 4.0 Era In Aceh, Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to identify the competencies and to develop a human resource development model for industry 4.0 in Aceh. To achieve the objectives, the study used a mixed-method research approach. Qualitative research was conducted through in-depth interviews with human resource development practitioners and experts who were selected purposively. While quantitative research was carried out by surveying 337 respondents who worked in various fields of work in Aceh. The results showed that there are 4 competencies needed to be able to compete and survive in industry 4.0, which are: (1) personal competence, (2) social competence, (3) methodological competence, and (4) technical competence. Of these four, personal competence has the greatest contribution in explaining the variants of competencies needed in the industrial revolution 4.0. For this reason, various elements of this personal competence should be prioritized in the human resource development model, followed by various other competencies, such as social competence, methodological competence, and technical competence. The development of these various competencies is expected to generate and transform Aceh's human capital into better superior human resources, who mastered and advanced in sciences, technology, and innovation as the main pillars of the regional development to achieve the Indonesia Golden Vision 2045.